STUDENTS' EFFORT FOR ACHIEVEMENT IN STRENGTHENING CONFIDENCE CHARACTER TOWARDS BODY SHAMING BEHAVIOR AT SMAN 1 GEDANGAN - Lailatin Rohmatun Nisa; Sarmini (JOSAR (Journal of Students Academic Research), 2022)
This study describes the efforts made by outstanding students at SMAN 1 Gedangan regarding strengthening the self-confidence character of the body shaming they experience. This study aims to analyze the efforts made by outstanding students at SMAN 1 Gedangan regarding strengthening their self-confidence character over the experience of body shaming. The theory used is the self-confidence theory by Peter Lauster. The type of research used is a qualitative approach with a case study research design. The data collection techniques in this study were in-depth interviews, observation, and documentation, with research informants selected using the criteria (1) outstanding students at SMAN 1 Gedangan, (2) aged 16-17 years, (3) had and or were experiencing behavior body shaming. The results of this study indicate that the presence of body shaming not make achieving students experience a bad impact, but the experience of body shaming becomes a source of strength for high achieving students to strengthen self-confidence through four efforts, namely (1) improving self-quality by honing competence and praying to God Almighty as a fortress of faith, (2) turning weakness into strength, (3) building self-construction of body shaming into a source of positive strength for students, (4) building self-esteem through achievement.